2017
DOI: 10.3389/fpubh.2017.00124
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Literacy among Community-Dwelling Older Adults in Urban China: A Cross-sectional Study

Abstract: ObjectiveDelay in seeking diagnosis of dementia is common in China. Misinformation and poor knowledge about dementia may contribute to it. The study was designed to explore the nationwide dementia literacy among older adults in urban China and to investigate the factors associated with overall dementia literacy.MethodsIn a cross-sectional study, a convenience sample of 3,439 community-dwelling old adults aged 60 and over was recruited from 34 cities in 20 provinces between June 20 and August 20, 2014. All part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 40 publications
5
51
2
2
Order By: Relevance
“…This finding echoed those of studies in developed countries such as Australia [6], Cambodia, Fiji and the Philippines [15], showing inadequate dementia literacy was prevalent in general. This study has filled the missing piece of puzzle in dementia literacy in China by providing further evidence of inadequate dementia literacy in community-dwelling adults (aged 18-64) in addition old adults (aged 65 or above) in China [11]. Public education to improve citizens' knowledge about dementia (which include the understanding of dementia symptoms, treatment options, care needs, and prognosis) and cultivate their positive attitudes towards dementia should be extensively supported.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This finding echoed those of studies in developed countries such as Australia [6], Cambodia, Fiji and the Philippines [15], showing inadequate dementia literacy was prevalent in general. This study has filled the missing piece of puzzle in dementia literacy in China by providing further evidence of inadequate dementia literacy in community-dwelling adults (aged 18-64) in addition old adults (aged 65 or above) in China [11]. Public education to improve citizens' knowledge about dementia (which include the understanding of dementia symptoms, treatment options, care needs, and prognosis) and cultivate their positive attitudes towards dementia should be extensively supported.…”
Section: Discussionmentioning
confidence: 92%
“…Another study indicated that majority of the respondents (77%) had personal fear of developing Alzheimer's Disease (AD) and being female, those with poor self-rated health, high proximity to AD and high perceived severity of AD were more likely to indicate such fear [10]. A recent study investigated the dementia literacy of older adults (aged 60 or above) living in 34 urban cities in China and found that their dementia literacy was very low [11]. The studies mentioned above had investigated the Chinese participants' basic knowledge about dementia, their intended actions if their own relatives suffered from dementia, their personal fear of developing dementia, and dementia literacy level of older adults.…”
Section: Introductionmentioning
confidence: 99%
“…China is one of those countries where the prevalence of dementia is growing rapidly; therefore, dementia literacy has become an important topic for discussion. The project team has identified three studies [9][10][11] on dementia literacy in China. A survey with 140 participants in the Chinese city of Tianjin showed that only 16% of the participants knew the risk factors of dementia and 56% were not sure whether they should share the diagnosis of dementia with the patients [9].…”
Section: Introductionmentioning
confidence: 99%
“…Another study indicated that the majority of the respondents (77%) had a personal fear of developing Alzheimer's Disease (AD), and that females, those with poor self-rated health, those in close proximity to someone with AD, and those with a high perception of the severity of AD, were more likely to indicate such a fear [10]. A recent study investigated the dementia literacy of older adults (those aged 60 or above) living in 34 urban cities in China and found that their dementia literacy was very low [11]. The studies mentioned above had investigated the Chinese participants' basic knowledge of dementia, their intended actions if their own relatives were to suffer from dementia, their personal fear of developing dementia, and the dementia literacy level of older adults.…”
Section: Introductionmentioning
confidence: 99%
“…, Mkhonto and Hanssen , Zhang et al . ). The ethnicity‐focused dementia awareness trope is also much broader than the assessment of knowledge.…”
Section: Awareness Research and The Ethnic Turnmentioning
confidence: 97%